Socialization Digital Marketing Through Social Media In Increase Business Income of the Padang Tualang Village Community Regency Step up - Siregar, Nurafrina (International Conference on Sciences Development and Technology, 2023)
This dedication is an application of the author's research conducted in July 202 3 , namely Socialization Digital Marketing Via Deep Social Media Increase Business Income of the Padang Tualang Village Community Regency step In this dedication the author will do socialization  Digital Marketing SME Entrepreneurship in Increase Incomeam public Village field Tualang. The use of digital technology has influenced all aspects of human activities, including marketing. Digital-based marketing is used to acquire consumers, build their preferences, promote brands, maintain consumers, and increase sales which ultimately increases profits. Digital marketing allows buyers to obtain all information about products and make transactions via the internet, and allows sellers to monitor and provide for the needs and desires of prospective buyers without time and geographic limitations. Digital marketing is also a two-way communication method that can raise public awareness and engagement towards certain products and brands. The platforms that are often used for digital marketing are social media, especially WhatsApp and Instagram. Method used _ that is Work observations on Community Service in Padang Tualang Village, Langkat Regency have an important role in understanding the situation and problems that exist in the village. By using the method This, It is hoped that the Community Service team can make a significant contribution in formulate program development Which in accordance with need And potency  village.